Hubungan Locus Of Control Dengan Social Loafing Mahasiswa UNP pada Tugas Kelompok - Wela Purwanalisia; Rinaldi (Jurnal Pendidikan Tambusai, 2020)
Social loafing is an individual effort that tends to decrease when working in groups working alone. The research aims to see if there is locus of control with UNP students on group assignments. The population of students from semester three to semester five in all faculties at Padang State University. A sample of 100 people can be taken, using purposive sampling technique in sampling. With two scales that are used as measuring instruments in the study, namely the social loafing scale (18 items, resulting in ? = 0.946) and the locus of control scale (14 items resulting in ? = 0.844). Multiple regression analysis, the existence of negative and positive guarantees as well as significant internal locus of control and social loafing (rxy = -0,296 and p = 0,000) means that high internal control environment results in low social loafing. Meanwhile, the significance between external locus of control and social loafing (rxy = 0.602 and p = 0.000) means that high external locus of control results in high social loafing as well.